IMPLEMENTASI THINK, TALK, WRITE (TTW) DENGAN KARTU “CERITA DALAM GENGGAMAN” UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS IV - Prasetyanti, Yulia Wulan; Untarti, Reni; Astuti, Sri Rahayu Puji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This Classroom Action Research was designed to improve the literacy skills of fourth-grade students at SD Negeri 2 Purwokerto Lor through the application of the Think, Talk, Write (TTW) Cooperative Learning model, supported by "Story in Hand" card media. The research was conducted in four cycles using the Kemmis-McTaggart spiral model, which included planning, action, observation, and reflection. The study involved 23 fourth-grade students as subjects, with data collected through tests. The research findings showed a significant improvement in literacy skills, especially in reading comprehension and writing skills. The percentage of reading comprehension mastery increased from 65% in Cycle I to 91% in Cycle III, while writing skills increased from 61% to 96%. The use of the TTW model facilitated students to Think critically, discuss, and Write in a structured manner, while the "Story in Hand" card media stimulated students' creativity and motivation. Obstacles such as limited research time and difficulty in maintaining student focus were noted for improvement. This study confirms that the combination of TTW and card media is effective for improving the literacy of elementary school students.